Dextran sulfate sodium-induced colitis and ginseng intervention altered oral pharmacokinetics of cyclosporine A in rats. (30th January 2021) - Yang, Ying; Hu, Nan; Gao, Xue-Jiao; Li, Ting; Yan, Zhi-Xiang; Wang, Pan-Pan; Wei, Bin; Li, Sai; Zhang, Zai-Jun; Li, Song-Lin; Yan, Ru
Abstract: Ethnopharmacological relevance: Application of cyclosporine A (CsA) as a rescue treatment in acute severe ulcerative colitis (UC) is limited by its narrow therapeutic window and great interpatient variability. As a substrate of cytochrome P450 3A enzyme (CYP3A) and P-glycoprotein (P-gp), the oral pharmacokinetics of CsA is susceptible to disease status and concomitant medications. Combined treatment with ginseng, a famous medicinal herb frequently prescribed for ameliorating abnormal immune response in many diseases including UC, showed immunologic safety in CsA-based immunosuppression. Aim of the study: Since the therapeutic levels of CsA can be achieved within 24 h, this study first assessed the impact of acute colitis and ginseng intervention on the single oral dose pharmacokinetics of CsA and explored the underlying mechanisms in dextran sulfate sodium (DSS)-induced colitis rats and Caco-2 cells. Materials and methods: Rats received drinking water (normal group), 5% DSS (UC group), or 5% DSS plus daily oral ginseng extract (GS+UC group). On day 7, GS+UC group only received an oral dose of CsA (5 mg/kg), while animals of normal or UC group received an oral, intravenous (1.25 mg/kg), or intraperitoneal dose of CsA (1.25 mg/kg), respectively. Blood, liver/intestine tissues and fecal samples were collected for determining CsA and main hydroxylated metabolite HO-CsA or measuring hepatic/intestinal CYP3A activity. Caco-2 cells were incubated with gut microbial culture supernatant (CS) of different groups or ginseng (decoction or polysaccharides), and then CYP3A, P-gp and tight junction (TJ) proteins were determined. Results: Oral CsA exhibited enhanced absorption, systemic exposure and tissue accumulation, and lower fecal excretion, while intravenous or intraperitoneal CsA showed lower systemic exposure and enhanced distribution, in colitis rats. Diminished intestinal and hepatic P-gp expression well explained the changes with DSS-induced colitis. Moreover, blood exposures of HO-CsA in both normal and colitis after oral dosing were significantly higher than intravenous/intraperitoneal dosing, supporting the dominant role of intestinal first-pass metabolism. Interestingly, colitis reduced CYP3A expression in intestine and liver but only potentiated intestinal CYP3A activity, causing higher oral systemic exposure of HO-CsA. Oral ginseng mitigated colitis-induced down-regulation of CYP3A and P-gp expression, facilitated HO-CsA production, biliary excretion and colonic sequestration of CsA, while not affected CsA oral systemic exposure. In Caco-2 cells, gut microbial CS from both colitis and GS+UC group diminished P-gp function, while ginseng polysaccharides directly affected ZO-1 distribution and suppressed TJ proteins expression, explaining unaltered oral CsA systemic exposure. Conclusions: DSS-induced colitis significantly altered oral CsA disposition through regulating intestinal and hepatic P-gp and CYP3A. One-week ginseng treatment enhanced colonic accumulation while not altered the systemic exposure of CsA after single oral dosing, indicating pharmacokinetic compatibility between the two medications. Graphical abstract: Image 1